FFECT OF QUEEN AGE AND BEE POPULATION IN NUMBOR OF QUEEN CEEL BUILDING BY HONEY BEE ( Apis Mellifera L.) COLONIES UNDER SULAIMANIA GOVERNORATE CONDITION/IRAQ - Sulaimn N.O.M; Ahmed H. Ameen; Muzahim A.Elsaiegh (Mesopotamia Journal of Agriculture)
The study had been conducted in Bazian Horticulture Station belonged to Sulaimani governorate on hybrid honeybees Apis mellifera L. kept in Italian hives model. The results of queen age and honeybee population evaluation on queen cell numbor during spring season showed that the highest mean of pre –constructed cells was 11.73 cells for QA1BP10 treat(= one year queen age with ten frames population) . and the lowest was 2.46 cells for QA2BP10 treat (= two years queen age with ten frames population). While the highest mean of Post constructed cells was 2.33 cells for QA1BP10 treat(= one year queen age with ten frames population). and the lowest was 0.06 cells for QA1BP5 treat (= one year queen age with five frames population). Results of early summer showed that the highest mean of pre – constructed cells was 127.93 cell for QA1BP10 treat. and the lowest was 21.53 cell for QA2BP5 treat. while the highest mean of Post – constructed cells was 30.92 cell for QA1BP10 treat. and the lowest was 2.79 cells for QA2BP10 treatBut results of the late summer showed that the highest mean of pre- constructed cells was 7.59 cell for QA2BP10 treat. and the lowest was 2.46 cell for QA2BP5 treat. while the highest mean of post- constructed cells was 5.06 cells for QA2BP2 treat. and the lowest was 0.93 cell for QA2BP5 treat(two years queen age with five frames population) .